2010
DOI: 10.1039/c0cc01762k
|View full text |Cite
|
Sign up to set email alerts
|

A simple chemical etching strategy to generate “ion-imprinted” sites on the surface of quantum dots for selective fluorescence turn-on detecting of metal ions

Abstract: A simple general chemical etching strategy is developed to generate "ion-imprinted" sites on the surface of QDs for subsequent selective signal turn-on detection of metal ions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
47
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(49 citation statements)
references
References 30 publications
1
47
0
1
Order By: Relevance
“…A triexponential luminescence decay ( Figure S2) and a decrease of luminescence lifetime with increasing Se(IV) were observed ( Table S1), indicating that the mechanism involved in the luminescence quenching is dynamic, and this agrees with previous works. 22,47 On the basis of the above discussions and the previous works, 22,45 we assumed that the binding between Cd in Cd−thiol complex and Se in H 2 Se on the surface of CdTe QDs might cause the increase of surface defects thus facilitate the nonradiative e − /h + recombination in the QD surface, which would eventually result in the fluorescence quenching of the CdTe QDs. Effect of HG Conditions.…”
Section: ■ Results and Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…A triexponential luminescence decay ( Figure S2) and a decrease of luminescence lifetime with increasing Se(IV) were observed ( Table S1), indicating that the mechanism involved in the luminescence quenching is dynamic, and this agrees with previous works. 22,47 On the basis of the above discussions and the previous works, 22,45 we assumed that the binding between Cd in Cd−thiol complex and Se in H 2 Se on the surface of CdTe QDs might cause the increase of surface defects thus facilitate the nonradiative e − /h + recombination in the QD surface, which would eventually result in the fluorescence quenching of the CdTe QDs. Effect of HG Conditions.…”
Section: ■ Results and Discussionmentioning
confidence: 90%
“…The structures of these clusters are shown in Figure 3, similar to previous studies. 43,44 The configurations and adsorption energies are also summarized in Figure 3 Previous studies reported 45,46 that a Cd−thiol complex surface layer was created as a shell around the CdTe QDs core to occupy the surface sites and to passivate the QDs. In addition, the binding force of Cd−Se bond was much greater than that of Cd-thiol.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An alternative approach to design uorescent sensors is based on the chemical etching effect, which originates from an etching reagent generating specic recognition sites on the surface of NPs for the selective turn-on detection of an absorber in the detection system. 35 This method can achieve enhanced sensitivity compared to other methods. However, CdTe NPs-based uorescent sensors using dithizone as the etching reagent for the simple detection of cadmium ion by turning the uorescence on have not been developed.…”
mentioning
confidence: 99%
“…62 The observation of fluorescence enhancement is less frequent, and in these cases the mechanism ascribed for the observed increase in quantum yield is the passivation of trap states or defects on the surface of the QDs. 63,64 In any case, the changes induced by the direct interaction between the metal ions and the QD's surface, unmodified or functionalized with a given ligand, have allowed the sensitive detection of several toxic metal ions.…”
Section: Quantum Dot As Passive Fluorescent Labelsmentioning
confidence: 99%